(untitled) (KULT_online, 2018)
In her pioneering work Novel Ontologies After 9/11. The Politics of Being in Contemporary Theory and U.S.-American Narrative Fiction, Elizabeth Kovach brings together literary investigation and the ontological turn in philosophy by critically approaching post-9/11 political realities mirrored in narrative fiction. The analysis of six recent U.S.-American novels oscillates around precarity rhetoric, neoliberal expansion, and surveillance ontologies. Those real-life concerns are demonstrated through a complex interplay between the narrative devices and “ontological dispositions” (p. 37) of the studied novels in concise argument. In her analyses, Kovach compares the degrees of convergence between current ontologies and the literary representations of the “state of grave concern” (p. 184) instilled in characters following neoliberal ravages.